THE INFLUENCE OF WORK DISCIPLINE, TURNOVER INTENTION AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT PT PAN BARUNA BATAM - Tio, Frankie; Husda, Nur Elfi (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2025)
This study aims to determine whether work discipline, turnover intention, and work motivation are influenced by employee performance at PT Pan Baruna Batam. The research method uses a descriptive quantitative method with a population and samples taken from respondents at PT with the approach used in the form of purposive sampling with a total sample of 102 people using saturated samples taken from all respondent results. The tests used in this study are validity, reliability, normality, multicollinearity, heteroscedasticity, multiple linear regression, coefficient determinants, and partial tests using the SPSS tool with version 29. The results of this test indicate that discipline has a significant and positive effect on employee performance, turnover intention has a significant and positive effect on employee performance, and work motivation has a significant and positive effect on employee performance.